Face pose estimation from eyes and mouth. (11th January 2010) - Shafi, M.; Chung, P.W.H.
Face pose estimation plays an important role in human computer interaction, automatic human behaviour analysis, gaze estimation, virtual reality, pose independent face recognition, etc. Accuracy and speed are the most desirable features of a face pose estimation system. In this paper, a face pose estimation scheme based on the centres of the eyes and mouth is proposed. The proposed method is simple and is, therefore, very effective in terms of computation because it uses only three points, i.e., eyes and mouth centres. The use of only three points increases the pose estimation range and makes the method suitable for real time applications. Tests using the Pointing '04 database show that the proposed scheme is robust and fast.